Children of absentee parents' level of self-esteem and concept of family as a social unit - Carbo, Anna Melissa J. (2003.)
This study aimed to describe the socio-demographic profile of the respondents; To determine the respondents' concept of family as a social unit; and to determine their levels of self-esteem. The 30 male and female students of the University of the Philippines in the Visayas, Miagao participated in the study. The study was conducted through administered questionnaire. Instrument used were the Rosenberg Self-esteem Scale and a second questionnaire that measured the degree of agreement with the conceptual definition of the family as a social unit. Scores from 26-40 in the Rosenberg Self-esteem Scale were considered as high and scores from 10-25 were considered as low. the second questionnaire used a five-level Likert scale to quantify their degree of agreement and the resulting mean/average was used to assess the degree of agreement of the respondents., Results went against the hypotheses that children of absentee parents had low self-esteem and that they had a different concept of the family as a social unit
Research Paper (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Parents; Children -- Self-Esteem.